The Materiality of Texts from Ancient Egypt, New Approaches to the Study of Textual Material from the Early Pharaonic to the Late Antique Period. - F.A.J. Hoogendijk; Steffie van Gompel (Volume Editors) (Papyrologica Lugduno-Batava, 2018)
The volume The Materiality of Texts from Ancient Egypt contains nine contributions from well-known papyrologists, Egyptologists, archaeologists and technical specialists. They discuss the materiality of ancient writing and writing supports in various ways through methodological considerations and through practical case studies from the early Pharaonic to the Late Antique periods in Egypt, including Greek and Egyptian papyri and ostraca, inscriptions and graffiti. The articles in this volume present new approaches to the study of textual material and scribal practice, especially in the light of the ongoing development of digital techniques that uncover new information from ancient writing materials. The aim of the book is to encourage researchers of ancient texts to consider the benefits of using these new methods and technological resources.